Channel modeling and performance test method for 5G - Guiming WEI; Xiang ZHANG; Yuhang GUO; Shangbing QIAO (Dianxin kexue)
With the rapid development of 5G wireless communication system, the throughput of 5G gNB and user equipment (UE) in the practical field environment is of great important.How to generate the accurate model in lab, which can represent the propogation condition in the field, has drawn great interests from both the academic and industrial communities.The channel modeling methods of 4G and 5G were introduced, and for 5G UE testing, the advantages of the multi-input multi-output (MIMO) and over-the-air (OTA) performance test solution were showed.Then, a detailed description of the OTA channel modeling principle and throughput simulation results were given in order to provide reference for related work.